The component parts of the first nominated Natural Heritage site for the Republic of Serbia - Jovanović Ivana; Dragišić Aleksandar; Ostojić Dragana; Krsteski Biljana (Zaštita prirode, 2019)
Natural World Heritage site of the Ancient and Primeval Beech Forests of the Carpathians and Other Regions of Europe (Albania, Austria, Belgium, Bulgaria, Croatia, Germany, Italy, Romania, Slovakia, Slovenia, Spain and Ukraine) aims to protect some of the last remnants of the natural and close-to-natural beech forests and to depict the beech postglacial spread throughout Europe. The Republic of Serbia is among 10 European countries to nominate extension components of this Pan-European World Heritage property, enhancing the representation of the Outstanding Universal Value by adding significant values to the existing property. This paper presents the characteristics of the nominated Serbian components, which include some notable pure-stand and mixed beech forests of great scientific and conservation value, protected by the strict protection regime for several decades as the integral parts of the Kopaonik, Tara and Fruška gora National Parks. Prepared nomination was submitted in January 2020 and is to result with the first Natural World Heritage property for the Republic of Serbia, thus strengthening the protection of individual sites and increasing awareness on their natural values.